THE SUCCESS OF ULTRASOUND GUIDED INSERTION OF CENTRAL VENOUS CATHETER VERSUS LANDMARK TECHNIQUE - Munir, Bilal; Naz, Fahim Ullah; Saleem, Salman; Khalid, Amna; Khan, Adnan Aqil; Din, Hassan Ud (Pakistan Armed Forces Medical Journal, 2021)
Objective: Central venous catheterization is an important skill for doctors working in the departments of medicine, surgery, critical care, anesthesiology, and emergency. The Agency for Healthcare Research and Quality, USA named ultrasound guidance of central venous catheter placement as one of 11 most underutilized practices that can enhance patient safety with greatest strength of evidence to provide clear opportunities for safety improvement. In this study, we compare the success of ultrasound-guided insertion of central venous catheter versus landmark technique. Study Design: Randomized controlled clinical trial. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi, from Jul to Dec 2016. Methodology: One hundred twenty patients admitted in its wards and undergone CVC were included. Patients were divided into group A & group B containing 60 patients each. In ‘group A’ CVC was done with ultrasound assistance while in ‘group B’ CVC was done with landmark technique. The primary study outcome was No. of attempts at which CVC was done. Results: In this study, 120 patients were enrolled. There was no difference in demographic data comparison. Success rate was found to be 28 (46.67%) in-group A while 16 (26.67%) in-group B with the p-value of 0.042 which is significant. Conclusion: We concluded that CVC with ultrasound guidance is more successful than landmark technique.